Type of Subtitling Strategies in Parker Movie - Wahyudi , I Made Panji Resa; Utami , Ni Made Verayanti; Hikmaharyanti , Putu Desi Anggerina (Journal of Language and Applied Linguistics, 2024)
The writer conducted research on the translation strategy used in the subtitled film "Parker" by Taylor Hackford. This research focuses on examining the various types of translation strategies discovered. The data in this study is analyzed using Gottlieb's (1992:166) theory of subtitling strategy. The data source is a DVD copy of the original film. Listening technique and note-taking technique were used to identify and classify the data. The unit of analysis in this research is every utterance that has a subtitling strategies and is classified into ten subtitling strategies contained in the film’s subtitle. The total data collected is 914 complete utterances in English and Indonesian. The results showed that there were only 8 strategies out of 10 strategies that were applied with the highest to lowest frequency : Transfer (71.11%). Imitation (313.67%), paraphrase (7.98%), condensation (3.61%), decimation (1.57%), deletion (1.20%). and others of less than 1%, such as expansion (0.65%), and transcription (0.21).